2012
DOI: 10.1089/ten.teb.2011.0365
|View full text |Cite
|
Sign up to set email alerts
|

Enamel Matrix Derivative: A Review of Cellular EffectsIn Vitroand a Model of Molecular Arrangement and Functioning

Abstract: EMD elicits a regenerative response in periodontal tissues that is only partly replicated by amelogenin or ameloblastin components. A synergistic effect among the various proteins and with the cells, as well as a temporal effect, may prove important aspects of the EMD response in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
114
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(122 citation statements)
references
References 192 publications
(330 reference statements)
7
114
0
1
Order By: Relevance
“…These proteins are important in the development of acellular cementum, the periodontal ligament, and alveolar bone. EMD has a variety of biological effects in vitro , such as regeneration of mesenchymal and epithelial cells, enhancement of wound healing via extracellular matrix synthesis, and the regulation of molecules involved in bone remodeling 1 , 8 . Genome-wide microarray approach demonstrated that EMD causes substantial alternations in gene expression, with similar patterns observed in palatal and gingival fibroblasts 11 .…”
Section: Introductionmentioning
confidence: 99%
“…These proteins are important in the development of acellular cementum, the periodontal ligament, and alveolar bone. EMD has a variety of biological effects in vitro , such as regeneration of mesenchymal and epithelial cells, enhancement of wound healing via extracellular matrix synthesis, and the regulation of molecules involved in bone remodeling 1 , 8 . Genome-wide microarray approach demonstrated that EMD causes substantial alternations in gene expression, with similar patterns observed in palatal and gingival fibroblasts 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Emdogain consists of enamel matrix derivatives and the vehicle propylene glycol alginate (Institut Straumann, Basel, Switzerland) [1]. The local application of Emdogain has been shown to support skin wound healing [2], [3].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, using recombinant AMELX and AMBN and transgenic mice that overexpressed EMPs and their splicing forms, previous studies have demonstrated that EMPs control cell adhesion, proliferation, polarity, commitment, differentiation and act on key-cellular pathways [18][22]. To date, nearly all the cells of dental-periodontal, epidermal and bone compartments have been found to respond to EMPs (for review, [23]). Transgenic mouse studies indicated that osteoblast and osteoclast cell activities are influenced by AMELX and AMBN [7], [24], [25].…”
Section: Introductionmentioning
confidence: 99%